2019
DOI: 10.3390/ijerph16183461
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Diabetes Prevalence, Awareness, Treatment and Control in Yangon Region, Myanmar, Between 2004 and 2014, Two Cross-Sectional Studies

Abstract: Myanmar is currently facing the burden of non-communicable diseases due to changes in lifestyle and dietary patterns linked to socio-economic development. However, evidence is scarce about changes in the prevalence of diabetes mellitus (DM) over time. We aimed to investigate changes in the prevalence, awareness, treatment and control of DM from 2004 to 2014, among adults aged 25–74 years, in the Yangon region. Two cross-sectional household-based studies, according to World Health Organization STEPwise approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(28 reference statements)
0
8
3
Order By: Relevance
“…23 Furthermore, no previous study measured the level of physical activity using a validated instrument like IPAQ-S in Yangon where the silent epidemic of diabetes is occurring amidst the trendy sedentary lifestyle and increasing motorization. 6,14 That was the reason why we conducted a case-control study in Yangon, performing an accurate measurement of PA and investigating its association with diabetes and risk factor especially age, reported in national STEP survey. 21 We set the eligibility criteria similar to national survey with a strict definition of case and control and being residents of Yangon to specify the study domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Furthermore, no previous study measured the level of physical activity using a validated instrument like IPAQ-S in Yangon where the silent epidemic of diabetes is occurring amidst the trendy sedentary lifestyle and increasing motorization. 6,14 That was the reason why we conducted a case-control study in Yangon, performing an accurate measurement of PA and investigating its association with diabetes and risk factor especially age, reported in national STEP survey. 21 We set the eligibility criteria similar to national survey with a strict definition of case and control and being residents of Yangon to specify the study domain.…”
Section: Discussionmentioning
confidence: 99%
“…5 According to the studies, using the results of the national survey conducted in Myanmar, applying World Health Organization STEPwise approach to surveillance (WHO-STEPS) in 2014, the prevalence of diabetes was 10.5% and impaired glucose tolerance was 19.7% for the adult population aged between 25 and 64 years. 6 The silent epidemic of diabetes is widespread in Myanmar, may bring many other noncommunicable diseases such as cardiovascular, strokes, disability, and deaths as its complications, resulting in heavy healthcare costs for this low-income country. Yangon Region, the most populated in Myanmar and the former capital is known to have the highest prevalence (18.2%) of diabetes in Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…The diabetic awareness rate among urban residents was higher than that among rural residents (92.8% vs . 68.4%, p < 0.001), which may be due to the limited health knowledge that is received in rural areas 19 , 20 . There is a study revealed that the increases in age and risks of developing hypertension and dyslipidemia, will correspondingly increase the opportunity of receiving disease-related medical education, which will improve diabetic awareness and treatment rates 10 .…”
Section: Discussionmentioning
confidence: 94%
“…Liver diseases, mainly due to overdose of rice, are increasing in Myanmar along with the improvement of living standard of the people [58] . More widespread intake of M. oleifera may help the prevention of NAFLD.…”
Section: Discussionmentioning
confidence: 99%